Association Between Obesity, Executive Functions, and Affective States: An Analysis of Patients from an Endocrinology Clinic - Sonia Rocío de la Portilla Maya; Dario Arturo de la Portilla Maya; Diana Marcela Montoya Londoño; Daniel Alfredo Landínez Martínez (Mediterranean Journal of Clinical Psychology)
Introduction: Obesity is a multifaceted public health concern with significant cognitive and emotional implications. This study explores the association between obesity, executive function deficits, and affective states in 26 patients (76.9% male; mean age = 41.3 years, SD = 13.0) from an endocrinology clinic in Manizales, Colombia.